Electronic gambling machine harm in older women: a public health determinants perspective. (2nd January 2022) - McCarthy, Simone; Pitt, Hannah; Bellringer, Maria E.; Thomas, Samantha L.
Abstract: Background: Women make up a significant proportion of all gamblers globally. However, there has been limited research which has explored women's gambling and the factors that may make women, and subgroups of women, vulnerable to harm. Methods: Using a Constructivist Grounded Theory approach, semistructured interviews were conducted with 20 women aged 55 years and over who regularly gambled on electronic gambling machines (EGMs). Results Key factors were identified to illustrate older women's experiences of gambling and are presented according to four determinants of health: Individual; socio-cultural; environmental; and commercial. While this research confirms that older women's gambling behaviors are strongly influenced by individual and socio-cultural factors, gambling environments, and industry practices are also influential. Conclusion A model illustrates the interplay of individual, socio-cultural, environmental, and commercial determinants, and the article proposes how they may contribute to gambling harm in older Australian women.